The Role of Protamine in Male Fertility - Aliakbari, Fereshteh; Abedi, Amir Reza; Rezaei-Tazangi, Fatemeh; Taghizabet, Neda (Archives of Men's Health, 2020)
Background: Approximately 40-50% of infertilities is related to males. Abnormal sperm chromatin structure is suggested as a significant cause of infertility. Protamines constitute a significant component of the sperm chromatin, and they play a vital role in the proper packaging of chromatin. Numerous studies have shown that protamine deficiency in sperm is associated with low sperm quality and infertility. Given the importance of protamine infertility, the purpose of this article is to investigate the content of protamine and its biological importance in male fertility. Materials and Methods: In this study, data and information collected on English-language articles from PubMed and MEDLINE databases. For Persian articles, Persian-language databases, including SID Scientific Database, IranMedex Medical Articles Database, IranDoc (Iran Scientific Information and Documents Research Institute), Magiran Publication Information and MedLib investigated. Results: Based on previous studies about protamine and its role in spermatogenesis, any disruption in protamine genes, including PRM1 and PMR2, can disrupt histone/protamine ratio, leading to abnormal spermatozoa. Conclusion: Most the previous studies approved any mutation in protamine genes correlates with infertility in men. These results can be a potential subject for future researches into infertility treatment in men.